1986
DOI: 10.1002/pi.4980180410
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of Composites Used in the Confinement of Nuclear Wastes 2 ‐ Water Absorption in Particle‐filled Epoxide Networks

Abstract: The diffusion of water into epoxide composites containing sand or glass beads has been studied as a function of temperature, type of filler and its surface treatment. This investigation falls within a broader context whose aim is to assess the possibility of embedding nuclear wastes into polymer matrices. The quality of polymer-filler adhesion was checked by scanning electron microscopy. The best filler was found to be siliceous sand in particles of about 30 p m diameter, which could be added to epoxide networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…While the strong interfacial bonding restricted the chain molecules mobility of polymer surrounding the filler particles, and then retarded the polymer molecular relaxation [12]. Nicaise et al [15] reported that when the adhesion of filler-matrix was strong, there was only one stage of absorption, but there were up to three stages of absorption for the poor adhesion of filler-matrix including: (i) displacement of low adhesion filler at the near saturation, (ii) progressive wetting of debonded particles and (iii) detachment of filler and accumulation of water around the filler. Those stages were more obvious for high content of filler.…”
Section: Introductionmentioning
confidence: 99%
“…While the strong interfacial bonding restricted the chain molecules mobility of polymer surrounding the filler particles, and then retarded the polymer molecular relaxation [12]. Nicaise et al [15] reported that when the adhesion of filler-matrix was strong, there was only one stage of absorption, but there were up to three stages of absorption for the poor adhesion of filler-matrix including: (i) displacement of low adhesion filler at the near saturation, (ii) progressive wetting of debonded particles and (iii) detachment of filler and accumulation of water around the filler. Those stages were more obvious for high content of filler.…”
Section: Introductionmentioning
confidence: 99%
“…It is also oserved that under cycles of wet and dry environment change, the interfacial properties are rapidly degraded due to significant variation of the residual adsorbed water in the interphase region [152]. This variation might be the result of the diffusion of water within the epoxy film through the micro-void created by the debonding processes [154]. The FTIR spectrum of the cured bisphenol-A-based epoxy resin is shown in fig.…”
Section: Fourier Transfer Infrared (Ftir) Spectroscopymentioning
confidence: 99%
“…Among them, thermoplastics and thermoset resins are efficient for the preservation of toxic substances, nuclear waste and fly ashes (Yasuo andShigeru, 1980a, 1980b;Nicaise et al, 1986aNicaise et al, , 1986bNicaise et al, , 1986cConner, 1990). The fly ashes from MSW solidified on polymer blends can be produced by extrusion, melt mold, or foam (Massadier et al, 1997;Leffilatre and Rodi, Report CEA-R-4378).…”
Section: Introductionmentioning
confidence: 98%